Analysis of the Principle of Cooperation in the My Little Pony Movie "Dragonshy" - Sari, Al Isa Maulida (DUTIES: Education and Humanities International Journal, 2025)
This research delves into the exploration of cooperation principles depicted in the animated film "My Little Pony: Dragonshy." Drawing upon the Cooperative Principle Theory proposed by linguist Paul Grice, which emphasizes the importance of communicative cooperation, the study investigates how the movie exemplifies these principles through conversation. Through qualitative analysis, the study identifies them into two types, namely the category of Non-Observance and the type of Maxim. In the category of Non-Observance, there are five, namely: Flouting a Maxim, Violating a Maxim, Opting Out a Maxim, Infringing a Maxim, and Suspending a Maxim. This category is mostly Violating a maxim. Then in the type of Maxim there are four, namely Maxim of Quality, Maxim of Quantity, Maxim of Relevance, and Maxim of Manner. The most common maxim violation observed is in the Maxim of Relevance. For the conversational implicature it is concluded that particularized is the most of the seven data results.